2019
DOI: 10.1038/s42255-019-0077-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic substrate cofeeding stimulates reductive metabolism

Abstract: Advanced bioproduct synthesis via reductive metabolism requires coordinating carbons, ATP, and reducing agents, which are generated with varying efficiencies depending on metabolic pathways. Substrate mixtures with shortcut access concurrently to multiple pathways may optimally satisfy these biosynthetic requirements. However, native regulation favoring preferential utilization precludes cells from co-metabolizing multiple substrates. Here we explore mixed substrate metabolism and tailor pathway usage to syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 47 publications
1
83
0
Order By: Relevance
“…To the best of our knowledge, this is the first report where supplementation of a substrate other than H 2 , increased productivities of continuous acetogenic CO 2 fermentation while maintaining net CO 2 utilization. Furthermore, the effect of CO supplementation on CO 2 utilization was superlinear, indicating a synergistic mechanism (Park et al, 2019). This is encouraging for development of bioprocesses valorizing CO 2 .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report where supplementation of a substrate other than H 2 , increased productivities of continuous acetogenic CO 2 fermentation while maintaining net CO 2 utilization. Furthermore, the effect of CO supplementation on CO 2 utilization was superlinear, indicating a synergistic mechanism (Park et al, 2019). This is encouraging for development of bioprocesses valorizing CO 2 .…”
Section: Discussionmentioning
confidence: 64%
“…Growth and acetate production was high but no characterization of the headspace was performed. More recently, continuous glucose-supplemented CO 2 /H 2 fermentation of Moorella thermoacetica by Park et al (2019) did not lead to net uptake of CO 2 . Furthermore, Jones et al (2016) did not show net CO 2 uptake for a wide range of acetogens (not A. woodii) fermenting syngas and fructose.…”
Section: Discussionmentioning
confidence: 99%
“…3). It has been shown that oxidizers can improve the oxidation of SCFAs (up to double speed) when superior NADPH and ATP generators (e.g., glucose) are consumed in small amounts to complement the stoichiometry through the pentose phosphate pathway (PPP) without triggering the shift of the entire cell's metabolism toward another substrate 38 . In this context, it is interesting to note that TEPI1 was the only MAG that encoded and expressed a hexose (allose) transporter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Metagenomic analysis was initially performed on the SEM1b community using two different generations that had consistent population structure and was used as a supporting database for a subsequent SEM1b time-series experiment. The time series analyses consisted of metabolomics, metaproteomics, and metatranscriptomics over nine time points (at t0, 8,13,18,23,28,33,38, and 43 h) in triplicate (A, B, and C), spanning the consortium life cycle (Fig. 1b).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that oxidizers can improve oxidization of SCFAs (up to double speed) when superior NADPH and ATP generators (e.g. glucose) are consumed in small amounts to complement the stoichiometry through the Pentose Phosphate Pathway (PPP) without triggering the shift of the entire cells metabolism toward another substrate 29 . In this context, it is interesting to note that TEPI1 was the only MAG that encoded and expressed a hexose (allose) transporter ( Fig.…”
Section: Interpretation Of Functional Specialization In the Light Of mentioning
confidence: 99%